2014
DOI: 10.1021/jf501941r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing on Phenolic Composition of Dough and Bread Fractions Made from Refined and Whole Wheat Flour of Three Wheat Varieties

Abstract: This study investigated the effect of breadmaking on the assay of phenolic acids from flour, dough, and bread fractions of three whole and refined wheat varieties. Comparison of the efficacy of two commonly used methods for hydrolysis and extraction of phenoilc acids showed that yields of total phenolic acids (TPA) were 5-17% higher among all varieties and flour types when samples were directly hydrolyzed in the presence of ascorbate and EDTA as compared to the method separating free, soluble conjugates and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 21 publications
5
43
1
Order By: Relevance
“…Ferulic acid was also prevalent in wheat flour (Supplementary Table 1). Previous reports also showed ferulic acid as the major phenolic compound in breads, with contents ranging from 3.4 mg/100 g to 8.2 mg/100 g, which were higher than that observed in the present study (2.3 mg/100 g) (Altunkaya et al 2013;Lu et al 2014). In both guava breads flavonoids accounted, on average, for 73% of total phenolics, being quercetin-3-O-rutinoside the major (56% on average), followed by ferulic acid (15% on average), quercetin (8% on average) and naringenin (8% on average).…”
Section: Soluble and Insoluble Phenolic Compoundscontrasting
confidence: 93%
See 1 more Smart Citation
“…Ferulic acid was also prevalent in wheat flour (Supplementary Table 1). Previous reports also showed ferulic acid as the major phenolic compound in breads, with contents ranging from 3.4 mg/100 g to 8.2 mg/100 g, which were higher than that observed in the present study (2.3 mg/100 g) (Altunkaya et al 2013;Lu et al 2014). In both guava breads flavonoids accounted, on average, for 73% of total phenolics, being quercetin-3-O-rutinoside the major (56% on average), followed by ferulic acid (15% on average), quercetin (8% on average) and naringenin (8% on average).…”
Section: Soluble and Insoluble Phenolic Compoundscontrasting
confidence: 93%
“…Phenolic contents in CB (6.2 mg/100 g) were similar to those previously reported in breads made with white wheat flour methods (3.4 mg/100 g to 11.1 mg/100 g) (Lu et al 2014;Menga et al 2010). The replacement of wheat flour by GP promoted a dose-dependent increase in phenolics contents guava breads (Table 1).…”
Section: Soluble and Insoluble Phenolic Compoundssupporting
confidence: 86%
“…The concentration of the total phenolic acids in all whole wheat bread fractions were 5.5-to 9.8-fold greater than the corresponding refined wheat fractions. In addition, the results indicated that the upper crust fraction had higher levels of total phenolic acids than the dough and crumb fractions, suggesting that total phenolic acids content did not decrease significantly during baking (Lu, Fuerst et al, 2014;.…”
Section: Phenolic Compounds During Processingmentioning
confidence: 94%
“…Higher levels of phenolic compounds have been reported in the bran fraction as compared to the refined grain fraction that primarily comprises endosperm. In a recent study, it was reported that most of the phenolic acids existed in bound insoluble form (80%) as compared to free soluble form, and high concentrations of phenolic acids were detected in whole grain which contains the bran fraction (627.8-745.6 µg/g dry weight) as compared to the refined grain (66.0-97.0 µg/g dry weight) (Lu, Fuerst et al, 2014).…”
Section: Distribution Of Bioactive Phytochemicals In Wheatmentioning
confidence: 99%
“…For separation and quantitation, mainly high-performance liquid chromatography (HPLC) combined with different detectors, e.g., diode array detector [3,14,[16][17][18] or CoulArray detector [19], was applied. In recent studies, a diode array detector in combination with a mass spectrometer operating in the single ion monitoring (SIM) mode was used [20,21]. However, to date, results of the influence of different solvents and different extraction times on the efficacy of the extraction process are scarce.…”
mentioning
confidence: 99%